Hematological Abnormalities in Patients With Acute Viral Hepatitis A and B - Akarsu, Saadet; Erensoy, Ahmet; Elkiran, Ozlem; Kurt, Abdullah; Kurt, A. Nese Citak; Aygun, A. Denizmen (Aves Yayincilik, Ibrahim Kara, 2008)
Aim: Acute viral hepatitis A (HA) and B (HB) are currently widespread health problems in developing countries, where poor hygienic conditions are prevalent. Extrahepatic abnormalities which involve many organs and systems can accompany these infections. Therefore we wanted to determine the rate of hematological complications in our cases diagnosed as HA and HB. Material and Methods: Referral test results of a total of 322 cases hospitalized and monitored with diagnoses of HA (Group 1: 219 cases) and HB (Group 2: 103 cases) were analysed retrospectively. Diagnosis of HA was established by Anti-HAV IgM antibody positivity and diagnosis of HB by elevated liver function tests, HbsAg and HBeAg positivity. Results: Mean leukocyte (8.405 +/- 2.682/mm(3)), neutrophil (3.985 +/- 1.880/mm(3)), hemoglobin levels (12.7 +/- 1.4 g/dl) and platelet counts (339.149 +/- 123.578/mm(3)) were determined. The total rate of hematologcal abnormalities was 59.32 % ( HA 58 %, HB 61.6 %), while the rates of leukopenia (0.93 %), leukocytosis (20.81 %), neutropenia (6.21 %), anemia (15.52 %), thrombocytopenis (4.35 %) and thrombocytosis (11.49 %) were also assessed. No cases of pancytopenia was detected. Conclusion: Hematological abnormalities were seen in nearly half of the cases with HA and HB, which constitute important public health problems in our country. The rates of hematological abnormalities were similar in HA and HB.
Keywords: Acute hepatitis A; acute hepatitis B; extrahepatic abnormalities; anemia; thrombocytopenia; leukopenia; neutropenia